1998
DOI: 10.1007/s004420050561
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between water and nitrogen translocation in a rhizomatous sedge ( Carex flacca )

Abstract: In order to examine whether the translocation of water and nitrogen in clonal plants is interdependent, interramet translocation of these two resources was investigated in the greenhouse. Two-ramet systems of Carex flacca were imposed to different spatial patterns of water and nitrogen supply. The experimental design allowed to examine the effects of water heterogeneity on nitrogen sharing, and, vice versa, the effects of nitrogen heterogeneity on water sharing. Interramet translocation of both water and nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 46 publications
4
67
2
Order By: Relevance
“…This may perhaps partly explain why many higher plant species that inhabit coastal environment are clonal species, where stress reduction at the vegetation edges represents intra-specific facilitation. Such facilitation could be a special kind of division of labor, a process that has been well documented for many other process in clonal species (e.g., see De Kroon et al 1998, Charpentier and Stuefer 1999, Van Kleunen and Stuefer 1999, Pennings and Callaway 2000.…”
Section: Discussionmentioning
confidence: 91%
“…This may perhaps partly explain why many higher plant species that inhabit coastal environment are clonal species, where stress reduction at the vegetation edges represents intra-specific facilitation. Such facilitation could be a special kind of division of labor, a process that has been well documented for many other process in clonal species (e.g., see De Kroon et al 1998, Charpentier and Stuefer 1999, Van Kleunen and Stuefer 1999, Pennings and Callaway 2000.…”
Section: Discussionmentioning
confidence: 91%
“…Our integrators thus suffer a cost for allocation to poorer patches, which plasticity in allocation or limited integration could potentially ameliorate. Empirical studies have suggested that such a cost can be either present (Salzman & Parker 1985;de Kroon et al 1998) or insignificant, perhaps due to plant plasticity (Roiloa & Retuerto 2006) or partial integration (Slade & Hutchings 1987c). Plants also can avoid costs of supplementing ramets in poorer patches by avoiding growth there (Hartnett & Bazzaz 1983;Slade & Hutchings 1987a-c;Evans 1988;Sutherland & Stillman 1988;Evans & Cain 1995).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that water was more readily transported from the older PRG to the younger SRG. de Kroon et al (1998) studied resource sharing in a Carex flacca and showed that water was transported from mother to daughter ramets in a homogeneous environment. In our Hetero S ?…”
Section: Discussionmentioning
confidence: 99%